Power Rangers, the movie - Spicer, Bryan; Ashley, Karan; Bosch, Johnny Young; Cardenas, Steve; Frank, Jason David (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2003)
The Power Rangers may have met their match as they face off with the most sinister monster the galaxy has ever seen-- Ivan Ooze.
Anamorphic widescreen, letterbox.
Originally released as a motion picture in 1995.
Bonus features not rated.
Karan Ashley, Johnny Yong Bosch, Steve Cardenas, Jason David Frank.
Rated PG.
DVD ; Dolby digital, surround.
Keywords: Films for the hearing impaired; Fantasy films; Action and adventure films; Science fiction films; Children's films; Feature films